(untitled) (Journal of Hama University, 2024)
The aim of this research was to know the relationship between Psychological Hardness and Ergonomic and Psychological risks among workers at Fire brigade in the cities of Latakia and Jableh, it also knowing the level of Psychological Hardness and Ergonomic and Psychological risks for them, and the differences in Psychological Hardness and Ergonomic and Psychological risks according to rank and years of service among the sample members, The descriptive approach was used, the research sample included (145) workers at Fire brigade in the cities of Latakia and Jableh, The two questionnaires of Psychological Hardness and Ergonomic and Psychological risks prepared by the researcher, were applied to sample after verifying their psychometric properties, The results showed Negative relationship between Psychological Hardness and Ergonomic and Psychological risks, and also showed that the level of each of Psychological Hardness and Ergonomic and Psychological risks was high, as for the differences, the results showed that there were differences in Psychological Hardness according to years of service variable in favor of workers whose working longest years (more than 10 years), and according to rank variable in favor of crew commanders, as for the differences in Ergonomic and Psychological risks, the results showed that there were no differences in Ergonomic risks according to rank and years of service, and also showed that there were no differences in Psychological risks according to rank variable, while there were differences according to years of service variable in favor of workers whose working shortest years (less than 5 years)